Praktik Kepemimpinan dan Manajemen di Madrasah Al-Khairat Kendek, Banggai Laut, Sulawesi Tengah - Badarwan Badarwan; Husnu A. Salim (Shautut Tarbiyah, 2019)
This paper aims to provide an overview of: 1) leadership practices in Madrasah Al-Khairat Kendek, Banggai Laut; 2) management practices at Madrasah Al-Khairat Kendek, Banggai Laut; 3) Leadership strategy in managing of Madrasah Al-Khairat Kendek, Banggai Laut. The research uses descriptive qualitative research, where the data collection process is carried out through interviews, observations, and documentation studies. Data analysis is performed through the stages of reduction, display, and data verification. Testing the validity of the data is done through a process of triangulation, extension of observation and increased perseverance. The results showed that the leadership practices in Madrasah Al-Khairat Kendek were charismatic-transformational leadership, where the development of madrassas relied heavily on leadership figures. In terms of management, Madrasah Al-Khairat has implemented management functions which include planning, organizing, implementing and monitoring. While the leadership strategy in managing madrasas can be seen in the formulation of the vision and mission of Madrasah Al-Khairat Kendek. Keywords: Leadership, Management, Madrasah